Whole-Exome Sequencing Implicates Neuronal Calcium Channel with Familial Atrial Fibrillation - Vad, Oliver Bundgaard; Yan, Yannan; Denti, Federico; Ahlberg, Gustav; Refsgaard, Lena; Bomholtz, Sofia Hammami; Santos, Joana Larupa; Rasmussen, Simon; Haunsø, Stig; Svendsen, Jesper Hastrup; Christophersen, Ingrid Elizabeth; Schmitt, Nicole; et al. (Frontiers in Genetics, 2022)
Atrial Fibrillation (AF) is the most prevalent sustained cardiac arrhythmia, responsible for considerable morbidity and mortality. The heterogenic and complex pathogenesis of AF remains poorly understood, which contributes to the current limitation in effective treatments. We aimed to identify rare genetic variants associated with AF in patients with familial AF. Methods and results: We performed whole exome sequencing in a large family with familial AF and identified a rare variant in the gene CACNA1A c.5053G>A which co- segregated with AF. The gene encodes for the protein variants Ca V 2.1-V1686M, and is important in neuronal function. Functional characterization of the CACNA1A, using patch-clamp recordings on transiently transfected mammalian cells, revealed a modest loss-of-function of Ca V 2.1-V1686M. Conclusion: We identified a rare loss-of-function variant associated with AF in a gene previously linked with neuronal function. The results allude to a novel link between dysfunction of an ion channel previously associated with neuronal functions and increased risk of developing AF.